Robust Ghost Imaging Based on Degenerate Spontaneous Parametric Down-Conversion - 孔令军 司宇 刘瑞 王周祥 齐文荣 涂成厚 李勇男 王慧田 (Chinese physics letters, 2017)
In traditional ghost imaging, the entangled photon pairs produced from the spontaneous parametric down conversion （SPDC） process are used. There is an intrinsic disadvantage that the utilization efficiency of the photon pairs is very low. Inasmuch as all the correlated photon pairs produced by the degenerate SPDC process can be used to record the image of an object, the ghost imaging scheme we present here has a higher utilization efficiency of the photon pairs. We also investigate the robustness of our experimental scheme. The experimental results show that, no matter whether the photon-pair source is two light cones or two beam-like spots, the clear image of the object can be obtained. The slight rotation of the nonlinear crystal has no influence on the imaging quality. Our experimental results also demonstrate that when the part of the photon-pair source in the signal path or the idler path is blocked by unwanted things, the clear ghost image of the object can still be recorded.